Biodegradable adhesive tape and application thereof
By using polylactic acid as the substrate layer and aliphatic polyester as the adhesive layer in the tape, the problem of non-degradation of the existing tape is solved, and the complete biodegradation of the tape under compost conditions and normal use performance is achieved.
Patent Information
- Application Number
- CN202410084290.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-31
- Filing Date
- 2024-01-19
- Publication Date
- 2025-02-14
AI Technical Summary
The existing tapes are not degradable due to the undegradable base film material, which leads to environmental pollution and inconvenient recycling, and common adhesives cannot be biodegradable, reducing the overall biodegradation rate of the tape.
Polylactic acid is used as the base layer and aliphatic polyester is used as the adhesive layer to form a biodegradable adhesive through an esterification reaction.
The complete degradation of tape under industrial composting conditions is achieved, which meets the requirements of high biodecomposition rate, while maintaining the normal use performance of tape.
Smart Images

Figure BDA0004674210250000171 
Figure BDA0004674210250000172 
Figure BDA0004674210250000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesive tapes and adhesives, and in particular relates to a biodegradable adhesive tape and application thereof. Background Art
[0002] Adhesive tape, also known as adhesive tape, is a product made of cloth, paper, film, etc. as the base material. It is processed into a tape by evenly coating the adhesive on various base materials and then supplied as a reel. Adhesive tape is a conventional consumer product, which is a civilian consumable used for packaging and sealing, shielding and protection, medical plasters, etc. In recent years, with the development of my country's e-commerce express delivery industry, the use of adhesive tape has increased sharply. According to the data of the State Post Bureau, my country's annual express delivery business volume has exceeded 100 billion pieces. However, along with this, the resource consumption and environmental impact of express packaging materials have become increasingly prominent.
[0003] The common express tapes on the market are mainly made of BOPP film (biaxially oriented polypropylene film) as the base film. This film has good physical stability, high mechanical strength, good air tightness, high transparency and glossiness, and is a widely used packaging film. However, BOPP is a fossil-based plastic, and even after hundreds of years, it still cannot be completely degraded. In addition, because BOPP tape is not biodegradable, cartons with tape cannot be directly pulped, and the parts with tape need to be screened out, which not only generates a large amount of industrial waste, but also brings great inconvenience to the recycling of cartons.
[0004] In recent years, as people pay more attention to the environment, a variety of degradable tapes have appeared on the market. Common substrates are kraft paper, cellulose film and polylactic acid film. Kraft paper and cellulose film have been maturely used in tapes. Polylactic acid (PLA) is a new type of degradable polymer material with good biocompatibility and degradability, suitable for use as a disposable product. Polylactic acid film (BOPLA) prepared by biaxial stretching process has excellent transparency and high strength, which meets the requirements of tape. Polylactic acid is also a source of biomass, which reduces white pollution while also reducing carbon emissions. In recent years, with the growth of market demand and production capacity, the price of polylactic acid has dropped significantly, making it possible to use BOPLA as a tape substrate.
[0005] Patent CN116178916A discloses a biodegradable film, which has a heat shrinkage rate of less than 10% after being treated at 120°C for 30 minutes. The biodegradable film can meet the requirements for dimensional stability during coating and other processing, and can be applied to the field of adhesive tapes. However, when the biodegradable film is used in the field of adhesive tapes, it is necessary to apply an adhesive to give the tape stickiness, and common commercially available adhesives are not biodegradable. After coating, the overall biodegradability rate of the tape will be reduced. Summary of the invention
[0006] In view of the above problems, an object of the present invention is to provide a biodegradable tape that can be completely degraded under industrial composting conditions.
[0007] In order to solve the above problems, the present invention provides a biodegradable tape, characterized in that it comprises a base layer and an adhesive layer, wherein the base layer comprises polylactic acid and the adhesive layer comprises aliphatic polyester.
[0008] <Base material layer>
[0009] The substrate layer contains polylactic acid. The polylactic acid may be a homopolymer or copolymer of lactic acid. For the homopolymer of lactic acid, it is preferably composed of 80-100 mol% of L-lactic acid or D-lactic acid and 0-20 mol% of their respective enantiomers. For the copolymer of lactic acid, it is preferably composed of 85-99 mol% of L-lactic acid or D-lactic acid. Polylactic acid can be obtained by dehydration polycondensation using lactic acid and other substances as raw materials; it can also be obtained from lactide and other substances by ring-opening polymerization. Among them, as lactide, L-lactide, a cyclic dimer of L-lactic acid, D-lactide, a cyclic dimer of D-lactic acid, meso-lactide obtained by cyclic dimerization of D-lactic acid and L-lactic acid, or a racemic mixture of D-lactide and L-lactide, DL-lactide, can be listed. Any of the above lactides can be used in the present invention.
[0010] The substrate layer preferably contains 60% by weight or more of polylactic acid relative to the total weight of the substrate layer. By making the content of polylactic acid 60% by weight or more, the processing performance, mechanical properties, thermal properties and other performance of the substrate can be maintained. Furthermore, it is more preferably 70% by weight or more, and even more preferably 80% by weight or more.
[0011] Furthermore, in order to increase the biodegradation rate, improve the flexibility, elongation, thickness deviation and adhesion to the adhesive layer of the substrate film, the substrate layer preferably contains one or more aliphatic polyesters having a glass transition temperature of 20° C. or less. Examples of the aliphatic polyesters having a glass transition temperature of 20° C. or less include polyglycolic acid, polybutylene terephthalate adipate, polybutylene adipate succinate, polybutylene succinate, polycaprolactone, poly-3-hydroxybutyrate, copolymers of 3-hydroxybutyric acid and 3-hydroxyvaleric acid, copolymers of 3-hydroxybutyric acid and 3-hydroxycaproic acid, and copolymers of 3-hydroxybutyric acid and 4-hydroxybutyric acid.
[0012] The aliphatic polyester having a glass transition temperature of 20° C. or less may be contained in an amount of less than 40% by weight relative to the total weight of the substrate layer. By making the content of the aliphatic polyester having a glass transition temperature of 20° C. or less less than 40% by weight, the flexibility and elongation of the substrate layer can be improved. It is more preferably 30% by weight or less, and even more preferably 20% by weight or less.
[0013] Furthermore, in order to improve the biodegradation rate and the adhesion between the substrate layer and the adhesive layer, the substrate layer contains one or more dibasic acids having 3 to 12 carbon atoms. The content of the dibasic acid is preferably 3% by weight or less relative to the total weight of the substrate layer. When the content of the dibasic acid is greater than 3% by weight, the processing performance and mechanical properties, thermal properties and other performance of the biodegradable resin, as well as the storage stability tend to decrease.
[0014] Examples of the dibasic acid include one or more of succinic acid, glutaric acid, 2-methyl-2-hydroxysuccinic acid, propylsuccinic acid, glutaric acid, 2-methyl-glutaric acid, 3-methyl-glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, galactaric acid, 2-hydroxysuccinic acid, and methylenesuccinic acid.
[0015] Furthermore, in order to improve the film processing performance, the substrate layer may further contain a processing aid, such as zinc stearate, epoxy compounds, etc. The content of the processing aid is preferably 1 wt % or less relative to the total weight of the substrate layer.
[0016] In the present invention, the surface tension of the substrate layer is preferably 35 mN / m or less, so that the adhesive tape can be directly rewound on the substrate layer after coating without using a release film. As a method for adjusting the surface tension of the substrate layer, the substrate layer can be subjected to a release treatment before the adhesive is coated on the substrate layer. As a method for measuring the surface tension of the substrate layer, the surface tension of the substrate layer can be tested by using a dyne pen.
[0017] <Adhesive Layer>
[0018] The adhesive used in the adhesive layer of the present invention contains an aliphatic polyester, which has biodegradability while maintaining adhesiveness. The aliphatic polyester is polymerized by esterification reaction of polyol and dibasic acid.
[0019] Furthermore, the structural unit of the aliphatic polyester contains one or more dibasic acids having 3 to 12 carbon atoms, preferably one or more of adipic acid, terephthalic acid, succinic acid, azelaic acid, and sebacic acid.
[0020] Furthermore, in order to provide sufficient cohesive force required by the glue, the structural unit of the aliphatic polyester preferably contains two of the dibasic acids, and the molar ratio of the two dibasic acids is preferably 8:2 to 2:8, more preferably 8:2 to 5:5.
[0021] Furthermore, the structural unit of the aliphatic polyester contains one or more polyols, preferably one or more of glycerol and pentaerythritol.
[0022] Furthermore, in order to improve the cohesive force of the adhesive layer and thus improve the holding force, it is preferred that the aliphatic polyester in the adhesive layer is obtained by crosslinking a polyester prepolymer, and the viscosity of the polyester prepolymer at 100°C is ≥3500mPa.s. The reason is that when the viscosity of the polyester prepolymer at 100°C is ≥3500mPa.s, it means that the molecular weight of the polyester prepolymer obtained by the esterification reaction is large enough, and the endpoint judgment standard of the esterification reaction is that the viscosity of the reaction product at 100°C reaches 3500mPa.s.
[0023] Furthermore, the structural unit of the aliphatic polyester contains an urethane bond. The urethane bond is produced by the reaction of an isocyanate curing agent with an aliphatic polyester. The urethane bond can be characterized by Fourier transform infrared spectroscopy (FTIR), and the characteristic peak of the cis-NH stretching vibration in the urethane bond is 3500 cm -1 As the isocyanate curing agent, IPDI curing agent, MDI curing agent, HDI trimer, TDI curing agent and the like can be cited. The amount of curing agent used is generally 1%-5%. The higher the curing agent content, the greater the degree of cross-linking of the adhesive, the lower the proportion of terminal hydroxyl groups, and the lower the initial adhesion.
[0024] <Biodegradable Tape>
[0025] The initial adhesion of the biodegradable tape of the present invention is greater than 14#, and the sustained adhesion is greater than 24hr. The initial adhesion is tested using an initial adhesion tester, and the test is performed according to the test standard of national standard YZ / T0160.2-2017. The test angle is 30°, and the prepared pressure-sensitive tape is cut into a strip of length×width 100mm×25mm, and the auxiliary rolling section is 100mm. A series of steel balls of different diameters are rolled down from the inclined plane. The initial adhesion of the sample is the maximum steel ball number that stops on the inclined plane. Each sample is tested 3 times, and the test result takes the middle value of the steel ball numbers of the 3 test results (the number of the test steel ball). According to the test standard of national standard YZ / T0160.2-2017, the adhesive strength test is carried out. The prepared pressure-sensitive adhesive tape is cut into 100mmx24mm strips and pasted on the test steel plate. It is rolled back and forth 3 times with a 2kg rubber-coated roller. After 20 minutes, it is hung on the test frame. A 1kg weight is hung at the hole under the steel plate. The time it takes for the tape to fall from the test steel plate is the adhesive strength of the sample. Each group of samples is measured three times, and the test result is the average of the time the tape falls from the same group.
[0026] The biodegradable adhesive tape of the present invention has industrial compost degradation performance. Specifically, under the composting condition of 58° C. specified in EN 13432, the disintegration rate in the first three months is more than 90%, and the biodegradation rate in the first six months is more than 90%.
[0027] Compared with the prior art, the biodegradable adhesive tape of the present invention uses BOPLA as the substrate layer, so that the substrate layer has degradability. The adhesive layer is formed by using degradable aliphatic polyester as a new adhesive, so that the adhesive tape has complete degradability while maintaining the performance. The biodegradable adhesive tape of the present invention can be used in sealing, binding, and packaging. DETAILED DESCRIPTION
[0028] Below, the technical scheme of the present invention is clearly and completely described by examples and comparative examples, but those skilled in the art will understand that the following described embodiments are part of the embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer.
[0029] The raw materials used in the embodiments and comparative examples are as follows:
[0030] Polylactic acid 1: manufactured by Total Corbion, specification: LX575.
[0031] Polylactic acid 2: manufactured by Total Corbion, specification: LX975.
[0032] Polycaprolactone: manufactured by Hunan Juren Chemical New Materials Co., Ltd., specification: 6500.
[0033] Sebacic acid: manufactured by China National Pharmaceutical Reagent Company, specification: AR.
[0034] Zinc stearate: manufactured by Aladdin Reagent Company, specification: AR.
[0035] Epoxy compound: manufactured by BASF, Germany, specification: Joncryl ADR 4468.
[0036] Glycerin: manufactured by Malaysia Natural Oil Chemicals Co., Ltd., specification: 99.7%.
[0037] Adipic acid: manufactured by Liaoyang Petrochemical Company, specification: industrial grade.
[0038] Curing agent: Made by Wanhua Chemical Group Co., Ltd., specification: Aquolin 161
[0039] The adhesive tapes obtained in the examples and comparative examples were tested by the following performance testing method.
[0040] 1. Surface tension
[0041] The surface tension of the substrate layer of the biodegradable tapes prepared in Examples 1-15 was tested using a dyne pen, and the results are recorded in Tables 1-3.
[0042] 2. Viscosity
[0043] The biodegradable tapes prepared in Examples 1-15 were tested for viscosity of the adhesive main agent at 100° C. using a rotational viscometer, and the results are recorded in Tables 1-3.
[0044] 3. Initial adhesion
[0045] The initial adhesion of the biodegradable tapes prepared in Examples 1-15 and the commercially available biodegradable tapes in Comparative Examples 1-3 was measured with reference to YZ / T0160.2-2017, and the ball numbers were recorded in Tables 1 to 3. The larger the ball number, the larger the ball diameter and the higher the initial adhesion.
[0046] 4. Holding force
[0047] The adhesion time of the biodegradable tapes prepared in Examples 1-15 and the commercially available biodegradable tapes in Comparative Examples 1-3 was measured with reference to YZ / T0160.2-2017, and the results are recorded in Tables 1 to 3.
[0048] 5.180° peel strength
[0049] The 180° peel strength of the biodegradable tapes prepared in Examples 1-15 and the commercially available biodegradable tapes in Comparative Examples 1-3 was measured with reference to YZ / T0160.2-2017, and the results are included in Tables 1 to 3.
[0050] 6. Tensile strength
[0051] The longitudinal tensile strength of the biodegradable tapes prepared in Examples 1-15 and the commercially available biodegradable tapes in Comparative Examples 1-3 was measured with reference to YZ / T0160.2-2017, and the results are included in Tables 1 to 3.
[0052] 7. Elongation at break
[0053] The elongation at break of the biodegradable tapes prepared in Examples 1-15 and the commercially available biodegradable tapes in Comparative Examples 1-3 was measured with reference to YZ / T0160.2-2017, and the results are included in Tables 1 to 3.
[0054] 8.Biodegradation rate
[0055] The biodegradable tapes prepared in Examples 1-15 and the commercially available biodegradable tapes in Comparative Examples 1-3 were measured for their biodegradability over 180 days under composting conditions at 58°C with reference to EN13432, and the results are given in Tables 1-3.
[0056] 9. Determination of urethane bonds
[0057] The aliphatic polyester prepolymer and the biodegradable adhesive prepared in Examples 1-15 were characterized by infrared spectroscopy, respectively, to confirm the characteristic peak of cis-NH stretching vibration in the urethane bond (3500cm -1 )’s existence.
[0058] Example 1
[0059] (1) Preparation of substrate layer
[0060] 49.5 parts of polylactic acid 1 (PLA), 49.5 parts of polylactic acid 2 (PLA), 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0061] (2) Preparation of adhesive layer
[0062] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The infrared spectrum showed the presence of urethane bonds.
[0063] (3) Preparation of degradable tape
[0064] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0065] Example 2
[0066] (1) Preparation of substrate layer
[0067] 42 parts of polylactic acid 1 (PLA), 42 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 0.8 parts of epoxy compound (ADR) and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0068] (2) Preparation of adhesive layer
[0069] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The infrared spectrum showed the presence of urethane bonds.
[0070] (3) Preparation of degradable tape
[0071] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0072] Example 3
[0073] (1) Preparation of substrate layer
[0074] 37 parts of polylactic acid 1 (PLA), 37 parts of polylactic acid 2 (PLA), 25 parts of polycaprolactone (PCL), 0.8 parts of epoxy compound (ADR) and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0075] (2) Preparation of adhesive layer
[0076] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The infrared spectrum showed the presence of urethane bonds.
[0077] (3) Preparation of degradable tape
[0078] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0079] Example 4
[0080] (1) Preparation of substrate layer
[0081] 32 parts of polylactic acid 1 (PLA), 32 parts of polylactic acid 2 (PLA), 35 parts of polycaprolactone (PCL), 0.8 parts of epoxy compound (ADR) and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0082] (2) Preparation of adhesive layer
[0083] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The infrared spectrum showed the presence of urethane bonds.
[0084] (3) Preparation of degradable tape
[0085] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0086] Example 5
[0087] (1) Preparation of substrate layer
[0088] 41.5 parts of polylactic acid 1 (PLA), 41.5 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 1 part of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extrusion cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0089] (2) Preparation of adhesive layer
[0090] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The infrared spectrum showed the presence of urethane bonds.
[0091] (3) Preparation of degradable tape
[0092] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0093] Example 6
[0094] (1) Preparation of substrate layer
[0095] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0096] (2) Preparation of adhesive layer
[0097] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The infrared spectrum showed the presence of urethane bonds.
[0098] (3) Preparation of degradable tape
[0099] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0100] Example 7
[0101] (1) Preparation of substrate layer
[0102] 40.5 parts of polylactic acid 1 (PLA), 40.5 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 3 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0103] (2) Preparation of adhesive layer
[0104] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The infrared spectrum showed the presence of urethane bonds.
[0105] (3) Preparation of degradable tape
[0106] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0107] Example 8
[0108] (1) Preparation of substrate layer
[0109] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0110] (2) Preparation of adhesive layer
[0111] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 2500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The presence of urethane bonds was measured by infrared spectroscopy.
[0112] (3) Preparation of degradable tape
[0113] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0114] Example 9
[0115] (1) Preparation of substrate layer
[0116] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0117] (2) Preparation of adhesive layer
[0118] 10 mol of glycerol and 10 mol of sebacic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 4500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The presence of urethane bonds was measured by infrared spectroscopy.
[0119] (3) Preparation of degradable tape
[0120] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0121] Example 10
[0122] (1) Preparation of substrate layer
[0123] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0124] (2) Preparation of adhesive layer
[0125] 10 mol of glycerol, 2 mol of sebacic acid and 8 mol of adipic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The presence of urethane bonds was measured by infrared spectroscopy.
[0126] (3) Preparation of degradable tape
[0127] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0128] Embodiment 11
[0129] (1) Preparation of substrate layer
[0130] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0131] (2) Preparation of adhesive layer
[0132] 10 mol of glycerol, 2.5 mol of sebacic acid and 7.5 mol of adipic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. Infrared spectroscopy showed the presence of urethane bonds.
[0133] (3) Preparation of degradable tape
[0134] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0135] Example 12
[0136] (1) Preparation of substrate layer
[0137] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0138] (2) Preparation of adhesive layer
[0139] 10 mol of glycerol, 5 mol of sebacic acid and 5 mol of adipic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The presence of urethane bonds was measured by infrared spectroscopy.
[0140] (3) Preparation of degradable tape
[0141] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0142] Embodiment 13
[0143] (1) Preparation of substrate layer
[0144] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0145] (2) Preparation of adhesive layer
[0146] 10 mol of glycerol, 7.5 mol of sebacic acid and 2.5 mol of adipic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 3 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The presence of urethane bonds was measured by infrared spectroscopy.
[0147] (3) Preparation of degradable tape
[0148] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0149] Embodiment 14
[0150] (1) Preparation of substrate layer
[0151] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0152] (2) Preparation of adhesive layer
[0153] 10 mol of glycerol, 7.5 mol of sebacic acid and 2.5 mol of adipic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 2 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The presence of urethane bonds was measured by infrared spectroscopy.
[0154] (3) Preparation of degradable tape
[0155] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0156] Embodiment 15
[0157] (1) Preparation of substrate layer
[0158] 41 parts of polylactic acid 1 (PLA), 41 parts of polylactic acid 2 (PLA), 15 parts of polycaprolactone (PCL), 2 parts of sebacic acid, 0.8 parts of epoxy compound (ADR), and 0.2 parts of zinc stearate were mixed and extruded into granules at 180°C. The mixture particles were extruded and cast and sequentially stretched in the transverse direction (MD) and in the longitudinal direction (TD) (MD×TD: 3×1.5) to obtain a substrate film. The semi-finished film was heat treated at a temperature of 130°C for 20 seconds.
[0159] (2) Preparation of adhesive layer
[0160] 10 mol of glycerol, 7.5 mol of sebacic acid and 2.5 mol of adipic acid were put into the reactor, the air was replaced with nitrogen, and the temperature was raised to 150-160°C for reaction. Samples were taken during the reaction, and the viscosity of the reaction product at 100°C was tested. The end point was 3500 mPa.s. After the reaction, the polyester prepolymer was taken out as the main agent of the glue, 4 phr of isocyanate curing agent Aquolin161 was added, and ethyl acetate was added to dilute the solid content to 40%, and the obtained solution was used as a polyester adhesive. The presence of urethane bonds was measured by infrared spectroscopy.
[0161] (3) Preparation of degradable tape
[0162] Silicone oil is coated on one side of the substrate layer to prepare a release layer; a polyester adhesive is coated on the other side of the substrate layer, and a biodegradable adhesive tape is obtained after drying.
[0163] Table 1
[0164]
[0165] Table 2
[0166]
[0167] Table 3
[0168]
[0169] Comparative Example 1 is a commercially available polylactic acid tape from Zhejiang Yonggu Adhesive Factory, Comparative Example 2 is a commercially available cellulose tape from Shandong Henglian Company, and Comparative Example 3 is a commercially available kraft paper tape from Shanghai Huayi Packaging Materials Co., Ltd. It can be seen from the test results of Tables 1 to 3 that the biodegradable tape prepared by the present invention meets the performance requirements and has a much higher biodegradability rate than commercially available biodegradable tapes. The performance parameters of the preferred solution are even better than those of commercially available biodegradable tapes.
[0170] According to the present invention, a biodegradable tape can be provided, which uses polylactic acid as a base material layer, so that the base material layer has biodegradability; and uses aliphatic polyester as an adhesive, so that the adhesive layer has biodegradability and a certain degree of adhesiveness, thereby not affecting the normal use function of the tape.
Claims
1. A biodegradable tape, characterized in that: The invention comprises a base material layer and an adhesive layer, wherein the base material layer comprises polylactic acid and the adhesive layer comprises an aliphatic polyester.
2. The biodegradable tape according to claim 1, characterized in that: The substrate layer contains 60% by weight or more of polylactic acid.
3. The biodegradable tape according to claim 1, characterized in that: The substrate layer contains one or more aliphatic polyesters having a glass transition temperature of 20° C. or less.
4. The biodegradable tape according to claim 1, characterized in that: The substrate layer contains 3 wt % or less of one or more dibasic acids having 3 to 12 carbon atoms.
5. The biodegradable tape according to claim 1, characterized in that: The structural unit of the aliphatic polyester in the adhesive layer contains one or more dibasic acids having 3 to 12 carbon atoms.
6. The biodegradable tape according to claim 1, characterized in that: The structural unit of the aliphatic polyester in the adhesive layer contains two types of dibasic acids having 3 to 12 carbon atoms, and the molar ratio of the two types is 8:2 to 2:
8.
7. The biodegradable tape according to claim 1, characterized in that: The structural unit of the aliphatic polyester in the adhesive layer contains at least one of glycerol and pentaerythritol.
8. The biodegradable tape according to claim 1, characterized in that: The structural unit of the aliphatic polyester in the adhesive layer contains a urethane bond.
9. The biodegradable tape according to claim 1, characterized in that: The aliphatic polyester in the adhesive layer is obtained by cross-linking a polyester prepolymer, and the viscosity of the polyester prepolymer at 100° C. is ≥3500 mPa.s.
10. The biodegradable tape according to claim 1, characterized in that: The surface tension of the substrate layer is 35 mN / m or less.
11. The biodegradable tape according to claim 1, characterized in that: The initial adhesion is greater than 14#, and the lasting adhesion is greater than 24hr.
12. The biodegradable tape according to claim 1, characterized in that: It has industrial compostable properties.
13. Use of the biodegradable tape according to any one of claims 1 to 12 in box sealing, binding and packaging.
Citation Information
Patent Citations
Biodegradable film, packaging material and adhesive tape
CN116178916A
Cited By
Production process of degradable antibacterial BOPP adhesive tape for food packaging
CN121873692A